Internalization of Prophetic Values in Entrepreneurial Activities at the TMI Al-Amien Prenduan (Girls' Campus) Islamic Boarding School, Sumenep, Madura (2024–2025) - Ghina Shafiyyah; Moh. Wardi (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to describe: (1) How is the application of the values of the Prophet Muhammad's character in entrepreneurship at the TMI Putri Al-Amien Prenduan Islamic boarding school? (2) How does the contribution of teachers/supervisors support the internalization of the Prophet Muhammad's character in entrepreneurship? To answer the question, the author uses a qualitative method. To describe the problems related to entrepreneurial activities at the TMI Putri Al-Amien Prenduan Sumenep Islamic Boarding School, because qualitative methods are used for observation, interviews, or document review, it facilitates direct contact between researchers and respondents. In theory, this study uses the FAST theory by Prof. Dr. Muhammad Syafii Antonio, Mec. The FAST theory is one of the concepts introduced by M. Syafii Antonio in his book "Muhammad: The Super Leader and Super Manager". This thesis concludes that first, the Al-Amien Prenduan Islamic Boarding School upholds Islamic values, so that everything, including the rules of the Islamic boarding school, is based on Islamic law. In terms of entrepreneurs, the Islamic boarding school applies the morals and characteristics of the Prophet Muhammad SAW in transactions, for example, students are taught to always be honest when selling products, amanah, tabligh and fathanah. Second, the role of supervisors or supervising teachers is very important. The supervising teacher will not only teach theory but also provide practical examples from everyday life. In entrepreneurial activities, the supervising teacher guides the female students to be honest (siddiq), responsible (amanah), communicate well (tabligh), think creatively and intelligently (fathanah).